MEMBANGUN BUDAYA TOLERANSI DI TENGAH PLURALITAS AGAMA DI INDONESIA - Yunus, Abd. Rahim (RIHLAH, 2013)
This paper offers the efforts to build tolerance in creating inter-religious harmony in the country of religious plurality. The effort was not enough simply through top-down policy with structural formalistic approach alone, but required tolerance that is bottom-up with a cultural approach. Tolerance for religious plurality nation can be implanted through a spirit of guidance and awareness of pluralism, nationalism, inclusivism, secularism, and the spirit and consciousness of human rights. With the spirit and consciousness, everybelieverwouldthink aboutthe substance ofreligionthatis universal, not at the pariatif partial and relative level. Beside having auniversalvalue, Religionalsohaskarakrteristikritualandpractice ofworshipor